(p-q)^4/(q-p)^3*(p-q)^2 计算
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 14:29:51
(p-q)^4/(q-p)^3*(p-q)^2计算(p-q)^4/(q-p)^3*(p-q)^2计算(p-q)^4/(q-p)^3*(p-q)^2计算(p-q)^4/(q-p)^3*(p-q)^2=(
(p-q)^4/(q-p)^3*(p-q)^2 计算
(p-q)^4/(q-p)^3*(p-q)^2 计算
(p-q)^4/(q-p)^3*(p-q)^2 计算
(p-q)^4/(q-p)^3*(p-q)^2
=(p-q)^4/[-(p-q)^3*(p-q)^2]
=-(p-q)^4/(p-q)^5
=-1/(p-q)
=1/(q-p)
√希望你能看懂,你能明白,赞同
(p-q)^4/(q-p)^3*(p-q)^2=(q-p)^4/(q-p)^3*(q-p)^2=(q-p)^(4-3+2)=(q-p)^3
前提q≠p
原式=(q-p)^4/(q-p)^3*(q-p)^2
=(q-p)^4/(q-p)^5
=1/(q-p)
(p-q)^4/(q-p)^3*(p-q)^2 计算
因式分解 6p+(p+q)-4q(p+q)
6p(p+q)-4q(p+q)如何因式分解?
4p(p-q)-6q(p-q)
6q(p+q)-4p(p+q)
因式分解 6p+(p+q)-4q(p+q)因式分解!!!!!!!!!
分解因式6p(p+q)-4q(p+q),
6q(q+p)-4p(q+p)等于多少?
6p(p+q)-4q(p+q)
分解因式,6p(p+q)-4q(p+q)
6p(p+q)-4q(p+q)
计算:(p-q)^2 * (p-q)^3 * (q-p)^5
(p-q)^5/(q-p)^2·(p-q)^3
(p+2q)(2p-q)-(p+q)(p-q)
p.q.
(p-q)^3*(q-p)^5计算
4(2p+3q)^2 -(3p-q)^2
(3p+2q)乘以(p+4q)等于多少